Peningkatan Ekonomi Kelompok Tani di Desa Daenaa melalui Inovasi Produk Kreatif Tortilla Chips dan Susu Jagung - Tangio, Julhim S; Husain, Rustam I.; Laliyo, Lukman Abdul Rauf; Mohamad, Erni; Kilo, Ahmad Kadir; Arwin, Muh (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
Corn is the main commodity product and the flagship of Gorontalo Province, ranked in the top 10 in Indonesia. In Daenaa Village, West Limboto Subdistrict, corn has not been maximally processed to increase creative economic growth due to limited knowledge and processing techniques, even though Daenaa Village is a corn production center in Gorontalo Regency. This community service activity aims to improve the skills and income of the residents of Daenaa Village, West Limboto District, through training in making processed corn products such as tortilla chips and corn milk. The training on making tortilla chips involves the process of boiling corn with lime water, mixing spices, adding corn flour, to shaping and drying to produce a durable ready-to-fry product. Meanwhile, the process of making corn milk includes boiling young corn, grinding, filtering, and adding sugar, flavor, and CMC to create a nutritious drink with a soft texture. The final product is hygienically packaged and labeled to increase its selling value. The results of the activity showed an increase in participants' knowledge and skills in processing corn into value-added products that have the potential to become micro-enterprises. Hopefully, this program can be the first step for the people of Daenaa Village to utilize local potential as a new source of sustainable income.